Advancements and Implications for Manual Therapy Techniques in the Management of Post-Concussion Syndrome - Negi, Baldev; Saini, Preeti; Rizvi, Moattar Raza (Disease and Health Research: New Insights Vol. 7, 2024)
This chapter describes an overview of the recent updates regarding the beneficial effects of various manual therapy techniques in the management of Post-Concussion Syndrome (PCS). It occurs due to a sudden blow to the head resulting in unconsciousness. The affected individual suffers from a varied range of symptoms like dizziness, headache, fatigue, and difficulty in concentrating. This syndrome is most commonly observed in the athletic population. The associated symptoms persist in the affected individual for up to many months, adversely affecting the performance of an athlete. There are a variety of treatment options available for its management including pharmacotherapy, psychological counseling, and physiotherapy. Manual therapy comes under the domain of physiotherapy including the skillful manipulation of soft tissues in order to achieve a desired therapeutic benefit. There are many kinds of manual therapy techniques such as craniosacral therapy, visceral manipulation, neural manipulation, and lymphatic drainage which are capable of inducing considerable relief from the symptoms associated with PCS. This recent update will provide valuable insight regarding the existing literature that supports the application of manual therapy in the resolution of symptoms following a concussion injury. It can be concluded that manual therapies can be utilized as a non-invasive alternative to management in individuals suffering from post-concussion syndrome. The findings can provide viable information regarding manual therapy management to practitioners dealing with sportspersons who are more prone to concussion injury.